Botulinum toxin and intractable trigeminal neuralgia - (:unkn) unknown (My University, 2005)
The effects of botulinum toxin have been demonstrated in pain syndromes such as migraine, tension headache, and postherpetic neuralgia. With this background data in hand, the authors planned a randomized, open-ended study to investigate the efficacy of botulinum injections in cases of refractory trigeminal neuralgia. In 8 patients with trigeminal neuralgia, 100 U botulinum toxin was injected into the region of the zygomatic arch. The results of their statistical analyses demonstrated that the medication can be effective in treating trigeminal neuralgia. The patients did not develop any significant adverse effects. Botulinum toxin can be used in the treatment of refractory trigeminal neuralgia. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Botulinum toxin; Treatment; Trigeminal neuralgia